Group simulation and income tax statistics: how big is the error? - Heiko Müller; Caren Sureth (Arbeitskreis Quantitative Steuerlehre (arqus), 2007)
Microsimulation based on income tax statistics may be useful in tax reform discussions. Unfortunately, access to appropriate data is still rather restricted and expensive for ad-hoc analyses, or individual data is often even not available at all. In this paper we take Germany and its data situation as a proxy for many countries' restrictions in terms of tax data availability. Analyzing how much reliability and robustness of results we lose if we employ group simulation instead of microsimulation, we compare both methods. Investigating tax scale effects by the group model leads to very good results. Determining the financial effects of modified tax bases, the deviation from the microsimulation results increases especially if tax base cuts vary between taxpayers. In addition, we take account of the class with taxpayers with a negative taxable income. Neglecting this class we identify a systematic underestimation of the financial consequences of a modified tax base with the group model assuming a progressive tax scale. If the group simulation data is not arranged according to the taxable income but rather according to the total amount of income we find in tendency higher deviations from the microsimulation results. Quantifying tax revenue effects of alternative tax settings the group simulation model represents a good compromise between the desire to capture the complex reality and the achievable accuracy when facing limited resources and data. Our group simulation model will be of major interest especially for analyses of rather old data, as sufficiently detailed data for micro analyses is usually missing.
Keywords: C81; H24; 330; microsimulation; group simulation; tax revenue; personal income tax; tax statistics; Einkommensteuerpolitik; Steuerreform; Steuerwirkung; Steueraufkommen; Simulation; Mikrosimulation; Steuerstatistik; Statistischer Fehler; Deutschland